Mappings between linguistic sound and motion - Cuskley, Christine (Public Journal of Semiotics, 2013)
This paper provides an overview of the possible function of non-arbitrary mappings between linguistic form and meaning, and presents new empirical evidence showing that shared cross-modal associations may underlie motion sound-symbolism in particular. In terms of function, several lines of empirical and theoretical evidence suggest that non-arbitrary form-meaning connections could have played a crucial role in lexical emergence during language evolution. Furthermore, the persistence of such non-arbitrariness in some areas of modern language may also be highly functional, as recent data has shown that non-arbitrary forms may help to bootstrap learning in children (Imai, Kita, Nagumo, and Okada, 2008) and adults (Nielsen and Rendall, 2012). Given the functional role of these non-arbitrary mappings between linguistic form and meaning, this paper describes new experimental data demonstrating shared mappings between non-sense words and visual motion using a direct matching task. Participants were given nonsense words that varied in terms of their voicing, reduplication, and vowel quality, and asked to change the movement of a ball to match a given word. Results show that back vowels are mapped onto slower speeds, and consonant reduplication with vowel alternation is mapped onto faster speeds. These results show a shared cross-modal association between linguistic sound and motion, which is likely leveraged in sound-symbolic systems found in natural language.